Persistent Courage of the Local Women Resistance Toward Undemocratic Policies - Titiek Kartika Hendrastiti; Sulistyowati Irianto (ETNOSIA : Jurnal Etnografi Indonesia, 2020)
This paper focuses on studying local women groups' resistance movement toward the policies regarding a permit for mining activities in their villages. Although locals have vehemently opposed this business, the official licenses to continue the activities are remain being issued by state authority and supported by the local government. This could be seen as a red flag from the policy that has been abandoned by local communities' interests. For the past decade, then being involved in social movements against undemocratic policies has sign significantly creased. There is no benefit for them from these policies, and local women also could see that their interests and knowledge have been ignored. The method used in this study is feminist ethnography, focusing on two villages as a location of mining activities. The first is Penago Baru in Seluma, Bengkulu, which has been exploited for their iron sand, then Praikaroku Jangga in Central Sumba, East Nusa Tenggara, as the location for gold mining. The study uses field-talks, in-depth interviews, live-in, thematic group discussions, and field-notes. The participants lived in a social movement or acted as indigenous leaders, NGO activists, and demics. The study shows the distinctive character of these local women communities, in which they tend to have a subaltern identity. As a subaltern community, they have never been considered to exist, as their interests are not included in the policy agenda-setting. Their resistance is actually a reflection of the state's ignorance of the locals' rights. The study also notes that local women communities in both locations are actually reliable agents of local environment knowledge, with their intimate experiences with surrounding nature. Their courage to resist these policies is more of an effort to protect the natural resources and the people, as well as the ecosystem.